Cognitive Impairments in LRRK2-Related Parkinson’s Disease: A Study in Chinese Individuals - Yifan Zheng; Zhong Pei; Yanmei Liu; Hongyan Zhou; Wenbiao Xian; Yingying Fang; Ling Chen; Qi Wu (Behavioural Neurology, 2015)
Background. LRRK2 S1647T has been identified as a polymorphic risk variant for Parkinson’s disease (PD) in Chinese individuals. As LRRK2 is the most common genetic cause for PD, it has drawn great interest regarding whether cognitive impairments in PD are related with LRRK2. Purpose. This study aimed to explore the effects of LRRK2 S1647T polymorphism on cognitive function in PD. Method. 90 PD patients were randomly recruited. They underwent a series of clinical evaluations and genetic testing for the LRRK2 S1647T polymorphism. Global intellect and five cognitive domains (language fluency, visuospatial function, attention, memory, and executive function) were compared between S1647T carriers and noncarriers. Results. No differences in motor features were found between two groups, but the executive function evaluation showed that Stroop word colour test time (SWCT-TIME) scores were lower in LRRK2 S1647T carriers than in noncarriers (P=0.017). However, multiple linear regression analysis indicated that the correlation between S1647T polymorphism and SWCT-TIME scores did not reach significant level (P=0.051). Conclusion. Our findings suggest that cognitive impairments are not correlated with different LRRK2 S1647T polymorphisms in Chinese PD individuals.